2015
DOI: 10.1159/000441570
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants in the Sex Hormone-Binding Globulin (SHBG) Gene Influence SHBG Levels in Women with Polycystic Ovary Syndrome

Abstract: Background: Decreased sex hormone-binding globulin (SHBG) levels were associated with polycystic ovary syndrome (PCOS). SHBG polymorphisms associated with reduced SHBG production were tested for their association with PCOS, but with inconclusive results. We tested whether altered SHBG levels and SHBG variants were associated with PCOS. Methods: The study subjects included 242 women with PCOS and 238 control women. SHBG genotyping was done by real-time PCR. Results: Higher minor allele frequency of rs13894, rs8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Family-based and case-control association studies have found that rs1799941 and rs727428 in SHBG gene influenced SHBG metabolism in American and Mediterranean women with PCOS [ 133 , 134 ], but not PCOS risk [ 133 ]. A recent study in Bahraini women has concluded that haplotypes spanning six polymorphisms were associated with either increased or decreased PCOS susceptibility [ 135 ] rekindling interest in SHBG gene polymorphisms in PCOS susceptibility.…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…Family-based and case-control association studies have found that rs1799941 and rs727428 in SHBG gene influenced SHBG metabolism in American and Mediterranean women with PCOS [ 133 , 134 ], but not PCOS risk [ 133 ]. A recent study in Bahraini women has concluded that haplotypes spanning six polymorphisms were associated with either increased or decreased PCOS susceptibility [ 135 ] rekindling interest in SHBG gene polymorphisms in PCOS susceptibility.…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…Primers shown in Table 1 were synthesized by Nanjing Lejin Biotechnology Co, Ltd (Nanjing, China), 17 and the PCR kit used in the study was purchased from Nanjing Jian Cheng Biotechnology Co, Ltd. A total of 20 μL reaction system was as follows: 1 μL DNA, 1 μL forward primer (10 pmol/mL), 1 μL reverse primer (10 pmol/mL), 10 μL PCR mixture, and 7 μL deionized water. The reaction conditions were as follows: predenaturation at 95°C for 5 minutes; and 35 cycles of denaturation at 95°C for 30 seconds, annealing at 62°C for 40 seconds, and extension at 72°C for 45 seconds, with final extension at 72°C for 10 minutes.…”
Section: Polymerase Chain Reaction-restriction Fragment Length Polymorphismmentioning
confidence: 99%
“…On the other hand, E326K, another missense polymorphism on exon eight, lowers SHBG levels and influences the SHBG metabolism independent of BMI, androgen, and insulin-related traits in PCOS women [ 69 ]. A recent study conducted in Bahraini women reported that specific SHBG variants affecting the SHBG concentrations and SHBG haplotypes spanning six polymorphisms were linked to increased or decreased PCOS susceptibility [ 183 ]. Thus, SHBG can be considered as a candidate gene playing a central role in the pathophysiology of PCOS.…”
Section: Shbgmentioning
confidence: 99%